Fluidity in the Early Formation of the Hebrew Bible - McDonald, Lee Martin 1942- (2020)
What follows is a survey of the formation of the Hebrew Bible in its formative stages, highlighting the continuing fluidity in the scope of the Jewish Scripture collection for centuries. This is seen from a limited selection of sacred texts in the post-exilic writing of Ezra and Nehemiah. To that time there was no formal fixed collection, though it is clear that most frequent citations or references are to the laws of Moses and likely all of the books of the Pentateuch. There are a few faint references to the Prophets (2 Kings and Ezra 5), but no clear reference to a collection of the Prophets until about 180 BCE in Ben Sira. Examples of this fluidity can be seen in several ancient Jewish texts (Dead Sea Scrolls, Philo, Josephus, and several early rabbinic texts) as well as in several early Christian references when Second Temple Judaism had a major influence on the Jewish-Christian sect, including the witness of several important Hebrew and Christian ancient manuscripts. These examples reflect the continuing fluidity in the shape of the Jewish Scriptures and the early Christian Old Testaments well into the Middle Ages.